Analisis Faktor-Faktor Kualitas Produk, Harga, Tempat, Dan Promosi Terhadap Keputusan Pembelian Di UMKM Martabak “ Mas Da’i ” - Adhi Widyakto; Nur Soleh; Dian Triyani; Rr. Lulus Prapti NSS (Universitas 45 Surabaya, 2023)
This study aims to analyze the factors of product quality, price, location, and promotion on purchasing decisions in UMKM Martabak Mas Da'i. The research method used was a survey using the purposive sampling method from 96 respondents who had made purchases at Martabak Mas Da'i. The collected data were analyzed using multiple linear regression analysis with the SPSS 26 program. The results of this study indicate that product quality, price, location, and promotion have a significant effect on purchasing decisions at Martabak Mas Da'i. Price has the most significant effect, followed by product quality, location, and promotion. These findings suggest that Martabak Mas Da'i should prioritize price of product quality and providing competitive product quality to attract more customers and increase sales